2007
DOI: 10.4067/s0717-95022007000100011
|View full text |Cite
|
Sign up to set email alerts
|

Relative Concentrations of Placental Lactogen II and PRL-Like Protein-A in Stressed Rats Placenta

Abstract: The chronic stress induces functional adaptations in the hypothalamo-pituitary-adrenocortical (HPA) and in the sympathetic-medullary-adrenal axis (SAM). Both axis are considered vital regulators of the homeostasis in vertebrates (Seyle, 1936; Ostrandrer et al., 2006. On the other hand, the placenta provides highly specialized functions during gestation that are critical for the normal development of the embryo/fetus (Soares et al., 1991). We hypothesized that the chronic immobilization (IMO) stress in pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…There are evidences that elevated levels of circulating maternal catecholamines could impair fetal development indirectly through placental vasoconstriction that reduces oxygen and nutrient supply to the fetus/es. 19,20 Romanini et al 21 concluded that the chronically stressed rats had activated the sympathetic-medullaryadrenal axis and increased the levels of catecholamine metabolite, acid 3-metoxi 4-hidroximandélico, in urines at the beginning of pregnancy. Also, high concentrations of corticotropin-releasing hormone (CRH) are found in growth-retarded fetuses and elevated maternal CRH levels are associated with decreased gestational length and increased risk of preterm delivery.…”
Section: Effect Of Prenatal Stress On Hypothalamicpituitary-adrenocormentioning
confidence: 99%
See 1 more Smart Citation
“…There are evidences that elevated levels of circulating maternal catecholamines could impair fetal development indirectly through placental vasoconstriction that reduces oxygen and nutrient supply to the fetus/es. 19,20 Romanini et al 21 concluded that the chronically stressed rats had activated the sympathetic-medullaryadrenal axis and increased the levels of catecholamine metabolite, acid 3-metoxi 4-hidroximandélico, in urines at the beginning of pregnancy. Also, high concentrations of corticotropin-releasing hormone (CRH) are found in growth-retarded fetuses and elevated maternal CRH levels are associated with decreased gestational length and increased risk of preterm delivery.…”
Section: Effect Of Prenatal Stress On Hypothalamicpituitary-adrenocormentioning
confidence: 99%
“…Table 1 summarizes the effect of prenatal stress and postnatal handling on selected endocrine and immune physiological parameters. 70 Lesage et al 15 Macrís et al 56 Romanini et al 21 Liaudat et al 43 Mayer et al 26 Desplats et al 71 Schroeder et al 28 Adrenal 70 Maccari et al 34 Meaney et al 55 Weinstock et al 69 McCormick et al 77 Smythe et al 70 Fenoglio et al 60 Total leucocytes ↓ Mayer et al 26 ↑ Liaudat et al 43 Liaudat et al 43 Llorente et al 78 Dhabbar et al 79 Lymphocytes number ↓ Llorente et al 78 ↑ Liaudat et al 43…”
Section: Postnatal Early Stimulation Attenuated the Immune System Supmentioning
confidence: 99%